Bioaugmentation strategies in co-composting anaerobically digested food waste with agricultural by-products: Enhancing fertilizer quality and microbial communities - Xuezhi Wang; Guyu You; Chenchen Liu; Yuan Sun (Ecotoxicology and Environmental Safety)
Effective management of urban solid waste is critical for achieving sustainable development goals. One key aspect of this challenge is the recycling of anaerobically digested residues from anaerobic digestion of food waste, which plays a pivotal role in promoting sustainability. However, there is a gap in understanding the feasibility and effectiveness of converting these digested residues into valuable fertilizers through composting. Addressing this gap, the present study explored the potential of composting anaerobically digested residue and evaluated the quality of the co-compost products. In this study, we investigated the composting process using a mixture of rice straw, food waste, sheep manure and mature composted residues (RFM group) alongside the anaerobically digested residues. The results demonstrated that the composting process quickly reached the thermophilic stage, during which NH+4-N concentrations increased and C/N ratio decrease. The RFM group exhibited the highest humic acid content compared to other groups. Additionally, microbial analysis revealed key species such as Clostridium, Moheibacter, Bacillus, Thermobacillus, and Pseudogracilibacillus as major contributors to the composting process. The germination index (GI) test indicated that the co-composted residues were non-toxic to plants, suggesting their suitability as a fertilizer. All these works indicated that the addition of rice straw, food waste, and mature composted residues to anaerobically digested materials significantly enhanced the composting process, resulting in a high-quality co-compost. This approach not only provided a promising method for recycling food waste but also contributed to the broader goal of sustainable solid waste management.